Mejora de los procesos de ensamble de la fábrica de congeladoras de la empresa BSH Electrodomésticos - Zavaleta Olivera, Janniret Karin Camila (2022)
The purpose of this research is to improve the production processes of the two main areas in the horizontal chest freezer factory of the company BSH Electrodomesticos, taking as a starting point a current analysis of the company, identifying points for improvement, and providing solutions that are reflected in the output indicators. Mainly, it was identified in the areas of cabinet foaming and assembly line, limited production capacity, work backlogs, limited workspaces, which did not allow to meet the market demand. The cabinet foaming area, the factory's bottleneck, with the improvement would double its capacity, producing 30 products per hour with four foaming injection machines and their independent manual loading. The customer area, the assembly line considered as the pacemaker area of production, had to meet a mix of freezer models and it would be possible with a single automated line with production schedules on demand. With the improvement, the assembly line would produce 24 products per hour, with a better distribution of activities in each workplace due to an adequate balance of activities; but with an important factor that is the respect for the ergonomics of the worker. With the improvement project, the company seeks to increase the capacity of its main areas of the Cooling factory, reducing waste and providing organized and safe work areas for its workers.